2022
DOI: 10.1016/j.heliyon.2022.e08788
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical modelling of mass transfer phenomena for sucrose and lactitol molecules during osmotic dehydration of cherries

Abstract: Effective diffusion coefficients were calculated in cherry flesh and skin. The fastest molecular movement is during the first hours of starting the process. Diffusivity of water and lactitol molecules is differential. Cherry skin acts as a barrier to the diffusivity of substances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The osmotic solution plays an essential role during osmodehydration: reducing water activity, helping to inhibit microbial growth, reducing enzymatic browning, and thus enhancing the food product characteristics. As a result, osmodehydrated foods may have a better appearance and taste than foods treated using different conservation methods (Cichowska et al, 2018; Maldonado & González Pacheco, 2022). For fruit dehydration, sucrose is frequently used as the osmotic solution.…”
Section: Introductionmentioning
confidence: 99%
“…The osmotic solution plays an essential role during osmodehydration: reducing water activity, helping to inhibit microbial growth, reducing enzymatic browning, and thus enhancing the food product characteristics. As a result, osmodehydrated foods may have a better appearance and taste than foods treated using different conservation methods (Cichowska et al, 2018; Maldonado & González Pacheco, 2022). For fruit dehydration, sucrose is frequently used as the osmotic solution.…”
Section: Introductionmentioning
confidence: 99%
“…The main variables that affect the mass transfer that occurs during OD are the concentration and temperature of the osmotic solution, the immersion time, the porosity of the food, the geometry, the composition of the solution, the pressure, the level of agitation, the dissolution-product relationship and the product pretreatment. Many of the mathematical models that predict osmotic dehydration are based on the application of the mass transfer process, which has been modeled based on Fickian diffusion theories, irreversible thermodynamics, and others (Maldonado & Gonzélez-Pacheco, 2022). However, ascorbic acid (AA) modeling in OD has not been established in the literature, so Page's equation was used through the finite cylinder model and a mathematical model by nonlinear regression for impregnation and its kinetic degradation, respectively.…”
mentioning
confidence: 99%
“…Moreover, it can be observed that the natural dye, red gardenia, demonstrated a greater redness than erythrosine at similar impregnation times, indicating a faster diffusion rate. This observation could be attributed to the smaller size and molecular weight of the natural red gardenia dye (388.37 g/mol) compared to that of the artificial dye erythrosine (879.86 g/mol) 42 , as mentioned earlier.…”
Section: A-f and G-l)mentioning
confidence: 53%
“…The findings also revealed that the red gardenia had more substantial effective diffusion coefficients, one order of magnitude greater in both cherry skin and flesh, with the main molecular movement of species in the system occurring up to approximately 40 minutes 41 . Contrary to erythrosine, the phenomenon stabilised after about 60 minutes, possibly due to the smaller size of the red gardenia molecule compared to erythrosine 42 . Furthermore, it was observed that the effective diffusion coefficients in cherry skin were one and up to two orders of magnitude lower than those obtained in cherry flesh (Fig.…”
Section: A-f and G-l)mentioning
confidence: 86%